Thermally Induced Valence Tautomeric Transition in a Two‐Dimensional Fe‐Tetraoxolene Honeycomb Network. (16th August 2018) - Chen, Jian; Sekine, Yoshihiro; Komatsumaru, Yuki; Hayami, Shinya; Miyasaka, Hitoshi
Abstract: A novel tetraoxolene‐bridged Fe two‐dimensional honeycomb layered compound, (NPr4 )2 [Fe2 (Cl2 An)3 ] ⋅2 (acetone)⋅H2 O (1 ), where Cl2 An n − =2, 5‐dichloro‐3, 6‐dihydroxy‐1, 4‐benzoquinonate and NPr4 + =tetrapropylammonium cation, has been synthesized. 1 revealed a thermally induced valence tautomeric transition at T 1/2 =236 K (cooling)/237 K (heating) between Fe m + ( m= 2 or 3) and Cl2 An n − ( n= 2 or 3) that induced valence modulations between [Fe II HS Fe III HS (Cl2 An 2− )2 (Cl2 An .3− )] 2− at T > T 1/2 and [Fe III HS Fe III HS (Cl2 An 2− )(Cl2 An .3− )2 ] 2− at T < T 1/2 . Even in a two‐dimensional network structure, the low‐temperature phase [Fe III HS Fe III HS (Cl2 An 2− )(Cl2 An .3− )2 ] 2− valence set can be regarded as a magnetic chain‐knit network, where ferrimagnetic Δ and Λ chains of [Fe III HS (Cl2 An .3− )]∞ are alternately linked by the diamagnetic Cl2 An 2− . This results in a slow magnetization behavior attributed to the structure acting as a single‐chain magnet at lower temperatures.